Electroacupuncture treatment ameliorates depressive-like behavior and cognitive dysfunction via CB1R dependent mitochondria biogenesis after experimental global cerebral ischemic stroke - Hu, Guangtao; Zhou, Cuihong; Wang, Jin; Ma, Xinxu; Ma, Hongzhe; Yu, Huan; Peng, Zhengwu; Huang, Jing; Cai, Min (Frontiers in Cellular Neuroscience, 2023)
This study aimed to identify the effect of electroacupuncture (EA) treatment on post-stroke depression (PSD) and explore whether cannabinoid receptor 1 (CB1R)-mediated mitochondrial biogenesis accounts for the treatment effect of EA. The PSD mouse model was induced by a consecutive 14-day chronic unpredictable stress operation after 7 days of recovery from the bilateral common carotid artery occlusion surgery. Either EA treatment or sham stimulation was performed for 14 consecutive days from Day 7 after the BCCAO operation. Subjects’ PSD-like behaviors were tested via open field test, sucrose preference test, novelty suppressed feeding test, tail suspension test, and forced swim test, and subjects’ cognitive function was examined using Y-maze and novelty object recognition test. In addition, the levels of CB1R, mitochondrial biogenesis-related proteins (nuclear transcription factor 1, NRF1; mitochondrial transcription factor A, TFAM), proteins related to mitochondrial function (Cytochrome C, Cyto C; AIF, COX IV), and mitochondrial DNA were measured. To elucidate the role of CB1R in EA treatment, CB1R antagonists AM251 and CB1R-shRNA were given to mice before EA treatment. Likewise, subjects’ depressive-like behaviors, cognitive function, mitochondrial function, and mitochondrial biogenesis were examined after the PSD procedure. Results showed that EA successfully ameliorated depressive-like behaviors, improved cognitive dysfunctions, and upregulated CB1R, NRF1 and TFAM expressions. However, the supplementation of AM251 and CB1R-shRNA blocked the antidepressant-like effects generated by EA, and EA failed to improve cognitive dysfunction, upregulate CB1R protein expression, and increase mitochondrial function and biogenesis. Altogether, these results indicated that EA ameliorated PSD-like behaviors in mice, improved cognitive dysfunctions after PSD, and promoted mitochondrial biogenesis by activating CB1R, a novel mechanism underlying EA’s antidepressant-like effects in treating PSD.